Enhancing organizational communication via intelligent voice assistant for knowledge workers: The role of perceived supervisor support, psychological capital, and employee wellbeing - Yin, Bin; Wu, Shu-Qi (Frontiers in Communication, 2023)
In the world of globalization, knowledge workers have grown in importance to organizational development. Currently, the intelligence voice assistant (IVA) has a high degree of participation in people's lives, displaying a trend of becoming an emotional partner for humans. Therefore, whether the application of IVA can help enhance organizational communication for knowledge workers is worthy to be explored. This study adopted an interactive situation-simulation survey experiment to explore the impact of the application of IVA on knowledge workers' perceived supervisor support, psychological capital, and employee wellbeing, using a 2 (voice gender: male/female) by 2 (voice characteristics: machine-like/anthropomorphic) between-subject experimental design with two additional control groups (text-only/no-interaction). Besides, voice interviews were designed to understand what knowledge workers need from the IVA. Results show that: (1) There were pair-wise correlations among perceived supervisor support, psychological capital, and employee wellbeing of knowledge workers, and psychological capital played a complete mediating role between perceived supervisor support and employee wellbeing; (2) There were significant differences among the scores of different groups (the experimental groups, the text-only control group and the no-interaction control group) on perceived supervisory support and employee wellbeing, with the experimental groups overall better than the control groups. (3) Knowledge workers hope that the services provided by the IVA mainly include three categories: work support, emotional support and life support. In conclusion, this study shows that the use of IVA can significantly improve perceived supervisor support, psychological capital, and employee wellbeing of knowledge workers, and provide some useful directions for the product design.